Public Sector Efficiency and the Functions of the Government - António Afonso; José Alves; Najat Bazah (CESifo GmbH, 2024)
We examine the relationship between public sector efficiency and government spending, to assess public resource management across the 27 European Union countries. Specifically, we analyze the growth of public expenditure in relation to outcomes across various public sector performance (PSP) indicators. We compute government spending efficiency using Data Envelopment Analysis (DEA) to subsequently assess the relationship between efficiency and the growth rate of public expenditure. Our findings suggest that higher efficiency can be achieved without proportionally increasing public spending, both in total expenditure and in specific areas such as social protection, economic affairs, education, healthcare, and public services. Indeed, with overall output efficiency scores between 0.77 and 0.87, with the same level of inputs, output could increase around 13%-23%. Additionally, public spending tends to rise during recessions, while it decreases with higher levels of human capital and redistribution indicators. Finally, more efficient countries tend to coalesce around Austria, Croatia, Denmark, France, Greece, Hungary, Poland, and Sweden.
Keywords: C33; C61; E62; H11; H50; O47; P43; 330; public sector performance indicators; efficiency; public expenditure; functions of the government; data envelopment analysis